Analysis of financial performance and risk profile of bank ocbc nisp in 2004-2008 - Fitra Purbasari (Indonesia Auditing Research Journal, 2021)
The purpose of this descriptive study is to find out the financial performance of a bank and its risk profile. The object of this research is OCBC NISP Bank with the observation period of five years from 2004 to 2008. This study is also comparing the size of banks and their ROE. The hypothesis of size and ROE were tested using the Independent Sample T-Test. Based on the research, the results are: the low ROE is caused by the lack of ability to collect funds, while the decrease in profitability is caused by the increase of high cost funds, and the low placement of assets. Credit risk, liquidity risk, interest rate risk, and capital risk of OCBC NISP Bank are quite low. The statistical analysis shows that there is a significant difference between the ROE of small banks and large banks.